Analysis of labour market migration in the OECD area - DAGO, Beugre Ange Emmanuel; YAO, Koffi Affoué Debora (International journal of economic perspectives, 2025)
This article examined the impact of migration on unemployment in 20 OECD countries over the period from 2000 to 2021. To initially investigate the existence of a long-term equilibrium relationship, the ARDL model was employed. The test revealed that, in general, an increase in the migration rate is associated with an increase in the unemployment rate in OECD countries. These results are fully consistent with the push and pull theory, which states that the arrival of migrants on the labour market as a complement promotes an increase in the unemployment rate. This implies that, in the presence of labour market rigidities, the arrival of immigrants can lead to an increase in unemployment in host countries. Secondly, the NARDL model was used to show the impact of a decline in migration on unemployment. The results showed that a decline in migration rates also leads to an increase in unemployment in OECD countries, but to a lesser extent. Thus, whether migration flows are low or high, they cause unemployment in host countries.